Pharmacognostical Aspects Of Calotropis Procera (Ait.) R. Br. - ANIL KUMAR SHARMA; RAJEEV KHARB; RAJANDEEP KAUR (International Journal of Pharma and Bio Sciences, 2011)
Medicinal plants have remained the major sources of drugs; in fact many of the currently available drugs were derived either directly or indirectly from them. The approach to new drugs through natural products has proved to be the single most successful strategy for the discovery of new drugs. In the past decade, research has been focused on scientific evaluation of traditional drugs of plant origin for the treatment of various diseases. Calotropis procera is small, erect and compact shrub, which is used in several traditional medicines to cure various diseases. This shrub has been known to possess analgesic, antitumor, antihelmintic, antioxidant, hepatoprotective, antidiarrhoeal, anticonvulsant, antimicrobial, oestrogenic, antinociceptive, and antimalarial activity. This review is a sincere attempt to summarize the information concerning pharmacognostical features of Calotropis procera shrubs.